The impact of endurance training on functional parameters during the preparation phase among cross-country skiers - Žiška, P.; Olasz, D.; Krcmár, M. (Acta Facultatis Educationis Physicae Universitatis Comenianae, 2016)
In the study, we have tried to demonstrate the effect of endurance training on changes in functional parameters during the preparation phase (12-week mesocycle) among cross-country skiers. The group consisted of 10 male cross-country skiers (age: 21.4 ±5 year) who completed control (1st 6 week mesocycle) and experimental period (2nd 6 week mesocycle).We focused on the following time-varying parameters: changes in maximal oxygen uptake (VO2max), the level of aerobic (AeT) and anaerobic thresholds (AT), maximum heart rate (HRmax) and performance on the running treadmill. The intra-individual monitoring of each athlete revealed statistical significance of VO2max (mid_VO2max = 69.48 ± 5.72 l.kg-1.min-1, post_ VO2max = 70.96 ± 5.67 ml.kg-1.min-1; p=0.05) and the level of AT (mid_AT = 86.2 ± 5.43 %, post_AT = 87.8 ± 5.59 %; p=0.01) the performance on the running treadmill (mid_t = 14:54 ± 1:43 min., post_t = 15:30 ± 1:50 min.; p=0.05).The significant changes were recorded in the AeT(pre_AeT = 70.3 ± 7.56 %, mid_AeT = 72.5 ± 7.59 %; p=0.05) in theHRmax(pre_HRmax = 190 ± 8.04 bpm, mid_HRmax = 189 bpm, post_HRmax = 188 ± 7.34 bpm; p = n.s.) during control period. We assume that the significant differences occurred as a result of adaptation changes due to training stimuli, which were induced by changes in functional parameters. Increased training volume in zone lower level of oxygen regime (A1), upper level of oxygen regime (A2) and upper level of lactate tolerance(T2) during experimental period elicited changes which reflected the increase functional parameters and performance on the running treadmill compared to that of control period.